Integrating Mind Mapping and Wordwall.net in English Learning for PE Students’ Vocabulary and Motivation - Febrianti, Mariska; Pradana, Ami; Putra, Aziiz Rahman (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This study examines how combining mind mapping with Wordwall.net can improve English vocabulary retention and learning motivation among Physical Education (PE) students. PE learners are often underrepresented in English Language Teaching research. The present approach integrates visual cognitive scaffolding with gamified learning to support active, learner-centered instruction. A mixed-method design involved 40 students from class A3, organized into eight groups. Data were collected through surveys, performance assessments, and semi-structured interviews. Findings showed vocabulary scores improved from pre-test averages of 55–60% to post-test averages of 73–82%, reflecting a 21–23% gain. Motivation indicators were also high: attitudes toward English (87.5%), peer and teacher influence (82.5%), and task value/enjoyment (85%). The combination of mind mapping and Wordwall.net effectively boosts vocabulary and motivation, providing practical strategies for ESP-oriented instruction in non-English programs. Keywords:‎ English learning; mind mapping; motivation; physical education students; vocabulary; wordwall.net